Effect of decreasing pressure on soliton self-compression in higher-order modes of a gas-filled capillary - Wan, Ying (2022)
We numerically investigate soliton self-compression in the higher-order modes of a gas-filled capillary with decreasing pressure. We demonstrate four times enhancement in the compression with the decreasing pressure compared to the equivalent constant pressure case in the HE12 mode, reaching sub-cycle duration of 1.85 fs at its output. Moreover, the negative pressure gradient effectively suppresses the intermodal coupling in the later stage of the compressor, which helps to maintain high output mode purity. These findings are of direct benefit for applications that require ultrashort light pulses in unconventional spatial beam profiles, including in nonlinear frequency conversion, microscopy, micromachining, and particle manipulation.